Students’ Perception on Online Application in Speaking Skill e-Learning - Rifari Baron (VELES Voices of English Language Education Society, 2020)
Online applications become a medium that helps the learning process of English in the classroom easier. Many online applications can be used to learn to speak English. Therefore, the aim of this study is to identify suitable online applications for learning to speak English that suits student needs. The research method uses descriptive qualitative. The data collection process is interview, observation, and questionnaire. Data analysis used three steps, namely data reduction, data display, and conclusion drawing. The results showed that the zoom and google hangouts meet is a popular video application. While website Youtube is a web application chosen interestingly for English speaking learning and social media WhatsApp is easy to use in English speaking learning. It is able to make a group. The implication of study is to increase teacher’s creativity to use the online application.